Pengaruh Tehnik Cerita Berantai TerhadapKeterampilan Berbicara Siswa Kelas V SDN 10 Kabila Kecamatan Kabila Kabupaten Bone Bolango - Halidu, Salma; Emmy, Aviqi Tirta (Dikmas: Jurnal Pendidikan Masyarakat dan Pengabdian, 2023)
This research is intended to find out The Effect Of Continuos Stroyting Technique On Students Speking Skill at Elmentary School SDN 10 Kabila, Kabila Subdistrict, Bone Bolange Regency. This is Fonsilated based on the problem of this research This pre-experimental research employed Car Grp Preiest design, and collected the data from observation, test, and documentation. The data were further alyzed by using copirical validity, normality testing, and hypothesis testing utilizing t-count testing. The result reveals that the continuous storytelling technique affects students' speaking skill in the site area. Thisis based on the average score of students' speaking in experimental class that is 41.83, while the control class reaches 37.43 The result of data analysis by employing t-test shows that 9.X and - 1.72 in the significance level of 5%. Therefore, 9.88 1.72, and the result is significant, meaning that His rejected and H, is accepted. It is concluded that there is an effect of continuous storytelling technique on students' speaking skill at Elementary School SDN 10 Kabila, Kabila Sub-district, Bone Bolango Regency.